Exploring associations between nutritional intake and cognitive performance in Spanish older adults - Lopez de Coca, Teresa; Bosch, Lourdes; Villagrasa, Victoria; Norgren, Jakob; Garcia-Ptacek, Sara; Moreno, Lucrecia (Frontiers in Nutrition, 2025)
BackgroundAs populations age globally, identifying modifiable dietary factors to support cognitive health has become a pressing research and public health priority. While specific nutrients have been linked to cognitive outcomes, few studies have explored the associations between habitual food group consumption on specific cognitive domains using standardized screening tools.MethodsTo investigate associations between dietary habits, relate to distinct cognitive domains in older adults by analyzing the food consumption in relation to memory, verbal fluency, and global mental status. Spearman correlation coefficients were employed to evaluate associations.ResultsSeveral nutrient-dense foods, such as nuts, extra virgin olive oil (EVOO), dark chocolate, and eggs, were linked to improved memory and verbal fluency. Conversely, higher intake of dairy products, refined grains, sugary products and red meat correlated with lower cognitive performance, particularly in verbal fluency. A higher proportion of saturated and trans fats, and proteins was inversely associated with cognition, while total fat and monounsaturated fatty acids (MUFA) intake showed positive associations, consistent with the protective role of EVOO.ConclusionThis study identifies specific, commonly consumed foods that correlate with cognitive function in aging adults. Given the cross-sectional design, associations should not be interpreted as causal, but they underscore the potential of food-based dietary strategies, rather than nutrients specific interventions, to preserve cognitive health and potentially delay age-related cognitive decline.